2020
DOI: 10.1007/s13197-020-04290-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-radiation on post-harvest storage life and quality of onion bulb under ambient condition

Abstract: Different doses of gamma Irradiation (0 Gy, 10 Gy, 60 Gy, 100 Gy and 200 Gy) were evaluated as potential treatment to extend the storage period and maintain the quality attributes of onion bulbs (cv. Punjab Noraya) at ambient temperature for a period of 144 days. It was observed that storage parameters such as physiological loss in weight, sprouting percentage, rotting percentage and quality traits like total soluble solids, firmness, color parameters, ascorbic acid and pyruvic acid varied significantly (p \ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…Physiological loss in weight (PLW) in both non-radiated and irradiated samples under low temperature was calculated according to the method adopted by Sharma et al (2020aSharma et al ( , 2020b as shown in formulae.…”
Section: Physiological Loss In Weight (%)mentioning
confidence: 99%
See 3 more Smart Citations
“…Physiological loss in weight (PLW) in both non-radiated and irradiated samples under low temperature was calculated according to the method adopted by Sharma et al (2020aSharma et al ( , 2020b as shown in formulae.…”
Section: Physiological Loss In Weight (%)mentioning
confidence: 99%
“…PLW ( % ) = (Initial weight of onion rings − weight of onion rings after interval of 5 days) × 100 Initial weight of rings . Sharma et al, 2020aSharma et al, , 2020bSharma et al, 2021). The texture analyzer was operated with a test speed of 1 mm/s having 1-mm depth of penetration and other operating parameters such as pre-test speed, post-test speed, return distance, contact weight, and return speed were standardized (Sharma et al, 2020a(Sharma et al, , 2020b.…”
Section: Physiological Loss In Weight (%)mentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the use of EOs, it is important to note the effect of radiation on its composition and activity. EOs are obtained mainly from fresh plant materials and gamma‐radiation is often employed as an alternative to reduce plant sprouting and/or ripening and can eliminate microorganisms, parasites, and pests [13] . In the world scenario, the radiation of natural products, mainly of food products, is a widely spread technique.…”
Section: Introductionmentioning
confidence: 99%